FAILURE ANALYSIS AND DESIGN MODIFICATION OF BRACKET OF CENTER BEARING OF PROPELLER SHAFT OF ST BUS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2017)
In the heavy transport vehicles basically front engine rear wheel drive type a propeller shaft is one of the most important component in transmitting power from the engine to the rear wheel drive. This propeller shaft is supported by the bracket fixed to the chassis. The center bearing bracket share about half overhanging portion of propeller shaft along with ball bearings. It enables reducing the length of propeller shaft to some extent.Fatiogue failure is a concern which may lead to the operational failure of the propeller shaft which ultimately results into the failure of transmission. Some common causes of failure are manufacturing ,design maintenance, raw material and the operating conditions. The aim of the this project is to find out the probable reason of the failure of bracket by analyze it with CAD software and to provide a satisfactory solution to this failure by changing dimension and material. This paper research is divided into two parts first to conduct survey amongst the buses & examine the causes of failure and second is to design and analyzed is recommended best possible alternatives of propeller shaft with the aid of advance design tool like CAD. Propeller shaft failure is one of the major problems facing for MSRTC workshop supervisors and Engineers.